Pengaruh Gerakan Shalat dan Faktor Lain Terhadap Kebugaran Jantung dan Paru pada Lansia - Siagian, Fitri Dyana; Boy, Elman (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2019)
Introduction: Over time, a person's age will increase in line with the decreasing cardiorespiratory fitness condition. Every human being certainly hopes to pass through the old age phase in a healthy and fit condition. For this reason, in order to improve cardiovascular fitness in the elderly, it is necessary to review what affects the decrease in cardiovascular fitness in the elderly so that later it can be modified for the better.Aims : To determine the effect of prayer movement and other factors on heart and lung fitness in the elderly.Method: This type of literature study is a literature review. The search strategy for English studies relevant to the topic was carried out using the ProQuest, SagePub, PubMed, Google Scholar, and Semantic Scholar databases limited from 2015 to 2020. The keywords used in the article search were elderly, influence, fitness, heart lung and prayer.Result: The factors that affect the fitness of the heart lung areheredity, age, gender, nutrition, smoking, physical activity and excessive salt consumption. Apart from that, the prayer movement can also improve blood circulation in the body and increase the supply of oxygen to the brain. Conclusion: There are many factors that affect cardiovascular fitness, some of which can be modified and cannot be modified. Meanwhile, the prayer movement is very beneficial for the health of the body both psychologically and mentally.